1994
DOI: 10.2307/3432231
|View full text |Cite
|
Sign up to set email alerts
|

Silica Radical-Induced DNA Damage and Lipid Peroxidation

Abstract: In recent years, more attention has been given to the mechanism of disease induction caused by the surface properties of minerals. In this respect, specific research needs to be focused on the biologic interactions of oxygen radicals generated by mineral particles resulting in cell injury and DNA damage leading to fibrogenesis and carcinogenesis. In this investigation, we used electron spin resonance (ESR) and spin trapping to study oxygen radical generation from aqueous suspensions of freshly fractured crysta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
36
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 17 publications
2
36
0
Order By: Relevance
“…In studies with artificial crystalline silica, the amount of exposed surface and size/shape of the particle also influenced cytotoxic potential [80]. Evidence strongly suggests that silica-derived ROS is directly responsible for in vitro DNA damage [81][82][83], various morphological changes including apoptosis in in vitro cell cultures [79,84,85], and acute lung damage in vivo [71]. The DNA damage is caused primarily by the hydroxyl radical, which is the by-product of iron contaminated silica [86].…”
Section: Particle-derived Free Radicalsmentioning
confidence: 99%
“…In studies with artificial crystalline silica, the amount of exposed surface and size/shape of the particle also influenced cytotoxic potential [80]. Evidence strongly suggests that silica-derived ROS is directly responsible for in vitro DNA damage [81][82][83], various morphological changes including apoptosis in in vitro cell cultures [79,84,85], and acute lung damage in vivo [71]. The DNA damage is caused primarily by the hydroxyl radical, which is the by-product of iron contaminated silica [86].…”
Section: Particle-derived Free Radicalsmentioning
confidence: 99%
“…Increasing evidence from epidemiological and animal studies has also implicated crystalline silica as a potential carcinogen (3,28,32,47). For example, inhalation of silica has been shown to cause lung tumors in rats (27)(28)(29)33).…”
mentioning
confidence: 99%
“…Previous studies have shown that silica causes direct DNA damage and mammalian cell transformation (10,11). Earlier studies have also demonstrated that FFSi 1 is capable of generating hydroxyl radicals ( ⅐ OH) upon reaction with aqueous media (12)(13)(14).…”
mentioning
confidence: 99%
“…The silicon-based free radicals (Si ⅐ , SiO ⅐ , and SiOO ⅐ ) and the associated generation of H 2 O 2 and ⅐ OH appear to be involved in the lipid peroxidation and membrane damage (12)(13)(14)(15). These radicals are also associated with silica-induced DNA damage, for example both strand breakage and hydroxylation of dG residues have been observed (10,17). O 2 .…”
mentioning
confidence: 99%